2023
DOI: 10.1186/s13046-023-02611-6
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multi-dimensional analysis highlights DHCR7 mutations involving in cholesterol biosynthesis and contributing therapy of gastric cancer

Abstract: Background Genetic background plays an important role in the occurrence and development of gastric cancer (GC). With the application of genome-wide association study (GWAS), an increasing number of tumor susceptibility genes in gastric cancer have been discovered. While little of them can be further applicated in clinical diagnosis and treatment due to the lack of in-depth analysis. Methods A GWAS of peripheral blood leukocytes from GC patients was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 53 publications
0
9
0
Order By: Relevance
“…Our results were similar to those in HeLa cells, and we explored the potential underlying mechanisms. DHCR7 has crucial functions in several malignant diseases such as gastric cancer [ 13 ] and colorectal cancer. [ 14 ] In this study, we found that the positive effect of TMEM147 on the proliferation, invasion, and migration of HCC cells mainly relies on DHCR7, which is related to the DHCR7-modulated cholesterol ester metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Our results were similar to those in HeLa cells, and we explored the potential underlying mechanisms. DHCR7 has crucial functions in several malignant diseases such as gastric cancer [ 13 ] and colorectal cancer. [ 14 ] In this study, we found that the positive effect of TMEM147 on the proliferation, invasion, and migration of HCC cells mainly relies on DHCR7, which is related to the DHCR7-modulated cholesterol ester metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Transwell migration and invasion experiments were conducted using the approach described in our previous study 17 . In the migration assay, a total of 3 × 10 4 GC cells were seeded in the upper compartments of a 24‐well plate (Corning, NY, USA, #353097) with an 8 μm pore size membrane.…”
Section: Methodsmentioning
confidence: 99%
“…Transwell migration and invasion experiments were conducted using the approach described in our previous study. 17 In the migration assay, a total of 3 × 10 4 GC cells were seeded in the upper compartments of a 24-well plate (Corning, NY, USA, #353097) with an 8 μm pore size membrane. The upper compartments were filled with 400 μL of serum-free media, while the bottom compartments were filled with 400 μL of media containing 20% FBS.…”
Section: Transwell Migration and Invasion Assaysmentioning
confidence: 99%
“…DHCR7 is already recognized as a risk factor in several tumors via regulating circulating vitamin D concentration, including ovarian cancer [ 18 ], nonmelanoma skin cancer [ 19 ], and thyroid cancer [ 20 ]. In addition, DHCR7 has been shown to be an oncogene and its high expression regulates the proliferation, migration, and invasion as well as apoptosis of tumor cells, such as in bladder cancer [ 21 ] and gastric cancer [ 22 ]. Additionally, DHCR7 is a vitamin D-related gene that interacts with 25(OH)D to increase the risk of BC [ 23 ].…”
Section: Introductionmentioning
confidence: 99%